(untitled) (Journal of Global Arts Studies, 2025)
Background: This article takes the Zheng concerto The King of West Chu as the research object and explores the application of historical themes in contemporary Zheng composition as well as its artistic value. Objective: This study aims to reveal the presentation of historical themes in music through an analysis of the work’s creative background, musical structure, and performance techniques. Methods: Composer He Zhanhao skillfully incorporated historical elements from Records of the Grand Historian (Shiji), particularly the biography of Xiang Yu, into the musical composition. Through distinctive guzheng performance techniques such as shaking, pressing, and vibrato, the work vividly portrays the heroic image of Xiang Yu and the dramatic atmosphere of the Battle of Gaixia. Results: The study focuses on the musical representation of historical figures, the depiction of historical scenes through musical expression, and the integration of musical language with historical narration. This fusion not only enriches the repertoire of the guzheng but also strengthens the cultural connotations embedded in the work. Conclusion: The study further explores the artistic value generated through the integration of historical themes and guzheng compositions, emphasizing that this innovative artistic form is of great significance for inheriting and promoting traditional Chinese culture. The research provides deeper interpretative perspectives for guzheng performers, offers new creative inspiration for composers, and serves as a reference for advancing the innovative development of traditional Chinese music in the new era.